A Case of Urachal Carcinoma of the Abdominal Wall in a Kidney Transplant Recipient - Takuya Yamazaki; Yasushi Nagaba; Yoshitaka Shimada; Yoshinori Taoka; Satoru Minamida; Dai Koguchi; Masahiro Hagiwara; Sho Watanuki; Hide Nagaba; Kazunari Yoshida; Yasuo Takeuchi (Case Reports in Medicine)
Urachal carcinoma is an extremely rare malignant tumor arising from the urachus in the fetus. We report a patient who developed urachal carcinoma 18 years after kidney transplantation. A 59-year-old man was admitted because of abdominal pain and massive ascites. He had undergone kidney transplantation 18 years earlier and had end-stage renal disease requiring dialysis. Abdominal CT showed massive ascites and an abdominal wall cystic mass separated from the peritoneal cavity. Hemodialysis was started, and paralytic ileus was diagnosed and treated. His ileus symptoms improved temporarily, but he died of myocardial infarction. An autopsy was performed, which revealed cystadenocarcinoma in the abdominal wall mass, leading to a diagnosis of urachal carcinoma.